Symposium 4: Learning Analytics in a Teachers' Social Network - Pham, Manh Cuong; Cao, Yiwei; Petrushyna, Zinayida; Klamma, Ralf (Proceedings of the International Conference on Networked Learning, 2012)
What is the social capital of a European teacher? We cannot give an answer for every teacher in Europe; but we have developed some measures for teachers participating in the eTwinning portal run by European Schoolnet as a case study. Driven by the idea that teachers collaborate across the borders with the support of an electronic platform, we were able to find correlations between social network analysis measures like degree and betweenness centrality as well as the local clustering coefficient, activity statistics about usage of eTwinning and the quality management of European Schoolnet. Only the combination of the three measures gives us indicators for the social capital gathered by a teacher. This learning analytics combines structural properties of the lifelong learning network of European teachers with the concrete usage statistics of a large-scale pedagogical social networking site using wall messages and blogs for communication among teachers and an established decentralized quality management framework which is unbiased by central policies. All work is implemented in a series of analysis and visualization prototypes working on anonymous data set extracted from the eTwinning network at certain time points. From this we can draw also on the evolution of the collaboration network as whole as well as on the development of the social capital of single teachers and their communities. As we have extracted different network structures mirroring the project and contact network of teachers and the online activities, we can compare the different factors contributing to the social capital of teachers.